AB0431 Earlier age at therapy initiation is associated with better response to tocilizumab therapy in patients with juvenile idiopathic polyarthritis. (12th June 2018) - Alexeeva, E.; Dvoryakovskaya, T.; Soloshenko, M.; Denisova, R.; Isaeva, K.; Mamutova, A.; Gladkikh, V.; Moskalev, A.
Abstract : Background: The use of therapy with anti-cytokine biologicals in routine practice has significantly increased the percentage of children showing good response to therapy and reduced the time to achieve pharmacological remission. Nevertheless, the problem related to selecting the optimal drug for a certain patient still remains to be solved. Objectives: This study was aimed at identifying clinical and laboratory parameters associated with response to tocilizumab (TOC) treatment in patients with RF-negative polyarticular JIA. Methods: The prospective study to assess TOC efficacy involved 55 patients with RF-negative polyarticular JIA aged 9.42 years (IQR 5.96–13.42), with females (85.5%) predominating was conducted at the National Medical Research Centre of Children's Health (Moscow). Treatment efficacy was evaluated using the ACRPedi criteria; Wallace's criteria were used to assess whether a patient had reached inactive disease or remission. The potential baseline characteristics associated with treatment response were identified using univariate and multivariate logistic regression analyses. Baseline factors included the clinical, laboratory, and anamnestic data. Results: TOC therapy showed high efficacy in children with RF-negative polyarticular JIA: 81.8/67.3/47.3/23.6% of patients reached the ACR30/50/70/90 criteria for the end of follow-up, respectively. The median time of achieving at least 30% improvement from baseline (ACR30) was 1 months (IQR 1:3). Univariate analysis showed that earlier age at initiation of Tocilizumab therapy, higher physician's global assessment score using the 100-point Visual Analogue Scale, and longer morning stiffness were the factors associated with reaching ACR90. Younger age at therapy initiation, greater number of swollen joints and joints with limited range of motion, and history of using fewer biologicals are the factors associated with reaching inactive disease and remission. However, multifactorial analysis showed that only earlier age at initiation of TOC therapy was a statistically significant factor associated with reaching the best response to therapy in all the models. Conclusions: Earlier initiation of TOC therapy is associated with higher chances for reaching ACR90 and pharmacological remission in patients with RF-negative polyarticular JIA. Further studies in larger cohorts are needed to identify the optimal age at therapy initiation. Disclosure of Interest: E. Alexeeva: None declared, T. Dvoryakovskaya Grant/research support from: Roche, Pfizer, M. Soloshenko: None declared, R. Denisova: None declared, K. Isaeva: None declared, A. Mamutova: None declared, V. Gladkikh: None declared, A. Moskalev: None declared